Multibeam Array Antenna with Compact Size Butler Matrix for Millimeter-Wave Application - Md Jizat, Noorlindawaty; Yamada, Yoshihide; Yusoff , Zubaida (International Journal of Integrated Engineering, 2023)
New radio wave technologies of millimeter-wave (mmWave), compact cell size, and multi beam base station are introduced with the recent development of the 5G mobile system. The Butler Matrix (BM) feed circuit is the most preferable candidate for the 5G mobile system since it can achieve multi beam radiation patterns at the array antenna, provide structural compactness and produce good multi beams. The BM circuit is typically built on a single dielectric substrate. However, in this single-substrate structure, the micro strip line connecting several circuit elements in the BM spans over a large area, resulting in significant feeding loss in the millimeter frequency band. In this study, a compact size circuit configuration of BM is proposed, where the original single-substrate structure is modified into a two-substrate stacking structure. The via-hole is designed to connect the two substrates with minimal path loss. The BM is built for the 28 GHz band with four inputs and four outputs. The phase delay is optimized using via-hole to produce the phase difference of ±45º and ±135º. The coupling for the hybrid is -3 dB, while the transmission coefficient of -6 ± 3 is achieved from the BM structure and, the return loss (Sii) for both input and output ports are less than -10 dB. The two-substrate BM is combined with the rectangular patch antenna and the via-hole patch antenna in a planar configuration of 0.5 ?0 spacing to obtain the radiation patterns. When the Port 1 through Port 4 of the BM are fed, four beams are created, with peak gains of 11.2 dBi, 9.87 dBi, 10.2 dBi, and 11.7 dBi, respectively, towards +16°, -35°, +39°, and -12°. The analysis includes the radiation performance from the ideal value and from the BM input. Three-dimensional representations of good multibeam radiation patterns are obtained after each input signal of the BM is fed.